PENGAWASAN HAKIM KONSTITUSI DALAM SISTEM PENGAWASAN HAKIM MENURUT UNDANG-UNDANG DASAR NEGARA RI 1945 - Titik TriwulanTutik (Faculty of Law, Universitas Jenderal Soedirman, 2012)
This research is normative legal research. The objective of this research is firstly to clarify whether the essence of constitutional court’s judges is not included in the term of judge in the 1945 constitution and Law number 24 2003 on judicial commission. Secondly, to know how model designs of controlling judges of constitutional court are after the issuance of Constitutional court’s decision Number 005/PUU-IV/2006. The conclusion of research are the judges of constitutional court are regular judges bound to all judge regulations in Indonesia, because Indonesian constitution does not recognize different typologies of judges, the note of PAH I BP MPR that formulated amendment of the 1945 constitution the discussion surrounding the typologies of judges never took place; and the legal scholars, generally tend to generalize judges to include judges of constitutional courts. The control of constitutional court necessary to adopt integrated control system, that is internal control is done by Constitutional Court and external supervision mechanism conducted by external independent department, it is Judicial Commission.Based on those findings, in implementing an integrated supervision mechanism of Constitutional Court’s Judges an amendment to the 1945 Constitution is recommended and revising the Law number 22 of 2004 on Judicial Commission and law number 24 of 2003 on Constitutional Court is urgently needed. Key words: control on justice of Constitutional Court, the system of judge control, an integrated supervision mechanism